The neural correlates of value representation: From single items to bundles. Issue 4 (28th November 2022) - Zyuzin, Jekaterina; Combs, Dalton; Monterosso, John R.; Brocas, Isabelle
Abstract: One of the core questions in Neuro‐economics is to determine where value is represented. To date, most studies have focused on simple options and identified the ventromedial prefrontal cortex (VMPFC) as the common value region. We report the findings of an fMRI study in which we asked participants to make pairwise comparisons involving options of varying complexity: single items (Control condition), bundles made of the same two single items (Scaling condition) and bundles made of two different single items (Bundling condition). We construct a measure of choice consistency to capture how coherent the choices of a participant are with one another. We also record brain activity while participants make these choices. We find that a common core of regions involving the left VMPFC, the left dorsolateral prefrontal cortex (DLPFC), regions associated with complex visual processing and the left cerebellum track value across all conditions. Also, regions in the DLPFC, the ventrolateral prefrontal cortex (VLPFC) and the cerebellum are differentially recruited across conditions. Last, variations in activity in VMPFC and DLPFC value‐tracking regions are associated with variations in choice consistency. This suggests that value based decision‐making recruits a core set of regions as well as specific regions based on task demands. Further, correlations between consistency and the magnitude of signal change with lateral portions of the PFC suggest the possibility that activity in these regions may play a causal role in decision quality. Abstract : We ask participants to make pairwise comparisons involving options of varying complexity: single items, bundles made of the same two single items and bundles made of two different single items. We find that a common core of regions involving the left ventromedial prefrontal cortex and the left dorsolateral prefrontal cortex is tracking value across all complexity levels. We also find that variations in activity in these regions are associated with variations in choice consistency, an effect most significant when options involve bundles made of different single items.